2014
DOI: 10.3390/socsci3040742
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Examination of Child Protection Initiatives in Sport Contexts

Abstract: Abstract:With the broadening of focus on child maltreatment beyond intra-familial settings, there is growing awareness of occurrences of maltreatment within the sport context. Millions of children participate in organized sport annually, and despite a tendency to view sport as a context by which to enhance the overall health and development of children, it is also a context in which children are vulnerable to experiences of maltreatment. The well-documented power ascribed to coaches, the unregulated nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…The participants in the current study highlighted education on power dynamics as a specific area of importance to advance safe sport. These notions are particularly relevant when considering that power differentials may place athletes in vulnerable situations where they are subjected to harmful experiences and the lack of attention currently given to power imbalances in safe sport education programs (Kerr et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The participants in the current study highlighted education on power dynamics as a specific area of importance to advance safe sport. These notions are particularly relevant when considering that power differentials may place athletes in vulnerable situations where they are subjected to harmful experiences and the lack of attention currently given to power imbalances in safe sport education programs (Kerr et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Young people often turn to the Internet for information (Kerr et al, 2014 ); SF websites may thus be an important source for educating, displaying, and normalizing the conversation about sexual abuse, as well as for sharing directions, resources, and support. For example, website content can contain information that is directly addressed to children and young people, which may help to empower and protect them against sexual abuse (Eliasson, 2017 ; Hartill et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The risks and harm of sexual abuse are affected by the inclination to disclose abuse and the kind of help and support that is offered—and reaches—those in need of it (Parent, 2011 ). Unfortunately, the literature reveals a history of ignorance and silence of sexual abuse in sport and governing agencies in sport rarely acknowledge or address sexual abuse (e.g., Parent and Hlimi, 2013 ; Brackenridge and Rhind, 2014 ; Kerr et al, 2014 ; Lang and Hartill, 2014 ; Mountjoy et al, 2016 ). Studies as well as sexual abuse cases reported in the media indicate that safeguarding measures in sports often fall short in protecting athletes (Parent and Demers, 2011 ; Mountjoy et al, 2016 ; Johansson and Lundqvist, 2017 ; Bjørnseth and Szabo, 2018 ; Kerr et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another effort to stimulate change, several organisations were created with the primary goal of raising awareness and/or enhancing education related to maltreatment in sport, including Canada's Respect in Sport and Speak Out, Australia's Play by the Rules, and the United States' Safe4Athletes, among others. Following these developments, Kerr et al (2014) examined seven international child protection in sport initiatives designed to enhance awareness of maltreatment and provide access to educational resources; they assessed the extent to which the initiatives were grounded in existing research and empirically evaluated in reference to their stated goals (i.e., awareness-raising and developing knowledge). The development of these initiatives was regarded as a positive step forward; however, the findings suggested that the initiatives were neither congruent with existing literature nor empirically evaluated.…”
Section: Introduction 1the Emergence Of the Safe Sport Movement In Re...mentioning
confidence: 99%